Influence of personality, religiosity, risk-taking, and counseling attitudes on cybersex engagement among postgraduate students in the Klang Valley, Malaysia - Ghoroghi, Soudabeh (2016)
With the popularity and reach of the Internet, accessing it for sexual purposes (cybersex) has been a growing concern. Since university students use the Internet as their main communication medium, their tendency to engage in cybersex-related activities ending in addiction is the major concern of this study. There is a dearth of academic models to fully explain the underlying factors involved in the development of cybersex addiction. So, this study developed a predictive model to enhance the understanding of cybersex by: (1) discussing and assessing hypotheses on the relationships between personality traits, religiosity and cybersex engagement; (2) examining the possible mediating role of risk taking and moderating effects of counseling attitudes and gender among the constructs; and (3) strengthening the internal validity of the causal model, control variables (time spent online, time spent for cybersex, and relationship status) included in the study. Utilizing a multistage proportional sampling, 256 postgraduate students who completed an online survey sent to their email addresses were randomly selected from five Malaysian universities. Gender was relatively evenly distributed, and education-wise, 50.4% of them were master and 49.6% PhD students aged 22-51 years. Empirical testing of the collected data was done using Partial Least Squares-Structural Equation Modeling (PLS-SEM), smart-PLS software version 3.0, which provided strong support for the proposed theoretical model by explaining 67% of variance in endogenous variables (47% of the variance in cybersex engagement and about 20% in risk taking). Statistically significant relationships were found to exist between personality traits (except agreeableness and conscientiousness) and religiosity with cybersex. Personality traits (except extraversion and neuroticism) and religiosity also showed statistically significant relationships with risk taking. There was a significant positive association between risk taking and cybersex engagement. Further, the influence of personality traits and religiosity on cybersex engagement was almost partially mediated by risk taking. Moreover, only agreeableness confirmed the moderating effect of counseling attitudes on the relationship between personality traits and cybersex engagement. Gender had no moderating effect on this relationship. Finally, the following were used as control variables in order to remove other possible explanations for the relationship between variables: time spent online, time spent online for cybersex, and relationship status. Only time spent online for cybersex had significant contribution to the cybersex engagement. Collectively, results of the study substantiated the notion that risk taking mediated several paths between personality traits and cybersex engagement. The results also supported some personality traits as predictor and the contention that religiosity provides a buffer against risk taking and cybersex engagement. University counselors would do well to be aware, and address the topic of cybersex and the probability of it becoming an addiction with serious life consequences for students.